1982
DOI: 10.1080/03079458208436088
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation against coccidiosis in chickens: Tests under simulated field conditions

Abstract: SUMMARYTwo trials designed to examine the effect of a vaccine against coccidiosis were carried out with commercial replacement layers. The effect of vaccination was evaluated by challenging vaccinated and non-vaccinated chickens. In the first trial chickens vaccinated at 14 days of age were compared with non-vaccinated, medicated chickens fed robenidine at 66 ppm throughout and with unmedicated chickens kept in the same house. In the second trial birds were vaccinated at 7 days of age and compared with non-vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…However, in birds partially immune to E. tenella the presence of severe caecal lesions may not necessarily be accompanied by lowered body weight gains (Long et al, 1980). Long et al (1982) also found lesions of E. tenella in commercial replacement layers that had been given TA oocysts when 2 weeks of age and then challenged with virulent strains 6 to 20 weeks later. It is possible that the administration in this study of a greater number of TA oocysts might have given better results, but a dose of 1 x 10 3 oocysts had previously been used by Long and Millard (1979) and by Long et al (1982) as a standard dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in birds partially immune to E. tenella the presence of severe caecal lesions may not necessarily be accompanied by lowered body weight gains (Long et al, 1980). Long et al (1982) also found lesions of E. tenella in commercial replacement layers that had been given TA oocysts when 2 weeks of age and then challenged with virulent strains 6 to 20 weeks later. It is possible that the administration in this study of a greater number of TA oocysts might have given better results, but a dose of 1 x 10 3 oocysts had previously been used by Long and Millard (1979) and by Long et al (1982) as a standard dose.…”
Section: Discussionmentioning
confidence: 99%
“…Long et al (1982) also found lesions of E. tenella in commercial replacement layers that had been given TA oocysts when 2 weeks of age and then challenged with virulent strains 6 to 20 weeks later. It is possible that the administration in this study of a greater number of TA oocysts might have given better results, but a dose of 1 x 10 3 oocysts had previously been used by Long and Millard (1979) and by Long et al (1982) as a standard dose. A precocious line of E. tenella recently selected by McDonald (personal communication) is being evaluated in this laboratory as a replacement for the TA line in a live attenuated vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Long (1972Long ( , 1973 also showed that the continuous passage of E. tenella in embryos resulted in an adaptation, associated with a reduction of pathogenicity, size of the schizonts (asexual stages) and a change in the site of development, compared with the original, 'parent' line of the parasite. Serial passage of E. tenella in embryonating chicken eggs usually results in the development of a line of parasite which is significantly less pathogenic to chickens compared with wild-type strains while remaining immunogenic (Long et al 1982). For these reasons, an egg-adapted line of E. tenella (derived after >100 passages) has been included in a commercial vaccine (Livacox ® ) (Shirley and Bedrnik 1997;Williams 2002a, b).…”
mentioning
confidence: 99%
“…Further experimentation is required to verify whether the pathogenicity and/or immunogenicity of E. tenella Rt3+15 in chickens change as it adapts to chicken embryos over a large number of passages and to establish its reproductive characteristics in embryos and, subsequently, in chickens. Since the serial passage of E. tenella in embryonating chicken eggs commonly results in the emergence of a line significantly less pathogenic in chickens compared with 'field strains' but immunogenic (Long et al 1982), an embryo-adapted line (after more than 100 passages) has been incorporated into the Livacox ® vaccine (Shirley and Bedrnik 1997). Eimeria tenella Rt3+15 has the potential to cause moderate caecal lesions in young chickens (Richards, unpublished).…”
mentioning
confidence: 99%